Effect of Multiatom Alcohols, Amides and DMSO on Grape and Potato Meristems Integrity - Shevchenko, N. A.; Strybul, T. F.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2004)
The authors investigated a toxic effect of glycerol, DMSO and substances of amide and diol series under various concentrations on potato and grape meristems. It is shown that the toxicity of the mentioned above substances under investigated concentrations is not stipulated by an osmotic factor and is intensified with increase of their hydrophobic properties.